On digraphs with a rooted tree structure - Szwarcfiter, Jayme Luiz (2017)
Submitted by Elaine Almeida (elaine.almeida@nce.ufrj.br) on 2017-03-08T17:32:32Z No. of bitstreams: 1 04-83_000040316.pdf: 314681 bytes, checksum: 091fd57a87d7f433d10e10b48a5ec9bf (MD5)